Pengaruh Kecuraman Gelombang Bangunan Bawah Air Geotube Terhadap Profil Pantai Pasir Buatan - Amaliah, Tuty (Jurusan Teknik Sipil Universitas Tadulako, 2017)
Beach damage is a serious problem which requires prompt action from the government. Adding more sediment to the beach (beach nourishment) is one of the efforts to cope with the problem. However, the sediment filled is usually carried away by the wave, which consequently brings maintenance costs for dealing with the sandpile during certain periods, as well as the need for large volume of excavation. One of the alternatives to reduce the loss of the sediment pile is by constructing off-shore submerged structure with the crest of the structure is set submerged and made from geotube. The objective of this study was to identify the influence of wave steepness to the beach profile formed behind the structure. The physical model test was carried out to the sand of Tanjung Ann beach (d50=1.47 mm) under two conditions: without the submerged structure and with the geotube submerged structure within wave period (1; 1.2; 1.4; 1.6; and 1.8 second), wave height (6,7,8,9,10,12,14, and 16 cm). The laboratory scale (small scale) was used. Model was placed in the wave channel with initial profile slope of 1:6 and was subject to constant regular wave until the beach profile balance was achieved. Results of this study showed that the beach profile slope was formed behind the geotube submerged structure and grouped into two zones: the swash zone and the breaking zone. The swash zone was where the highest run up and the lowest run down occurred and the breaking zone is where the Deanâ€™s formula applied. The influence of wave steepness (increasing Ho/Lo) was the increasing setback of the beach profile behind the geotube submerged structure. It would give benefit when the H0/L0 â‰¤ 0.068 for constant structure height.